A Walk in the Night with Zhuangzi Musings on an Ancient Chinese Manuscript. - Huang, Kuan-yun (State University of New York Press, 2023)
A complete translation and analysis of ""All Things Flow into Form"" (Fan wu liu xing), a recently discovered manuscript from the Warring States period (481-221 BCE).
Description based upon print version of record.
Keywords: Fan wu liu xing.; Philosophy, Chinese -- To 221 B.C.; Philosophie chinoise -- Jusqu'à 221 av. J.-C.; PHILOSOPHY / Taoist.; Philosophy, Chinese; To 221 B.C.